Evaluation of Utah's Early Intervention Mandate: Juvenile Sentencing Guidelines and Intermediate Sanctions, 1996-2000 - Van Vleet, Russell K. ([Verlag nicht ermittelbar], 2003)
This study was an evaluation of changes initiated by the State of Utah to reduce youth crime: a program of early intervention comprised of Juvenile Sentencing Guidelines and a new intermediate sanction called State Supervision. Together, the Sentencing Guidelines and State Supervision sanction were designed to bring about a reduction in juvenile recidivism rates and subsequently reduce the number of offenders placed out of the home in the custody of the Division of Youth Corrections by 5 percent. Researchers combined quantitative measures of sentencing guidelines compliance and recidivism rates with qualitative interviews of juvenile justice system personnel and youth offenders. Data were gathered on all offenders receiving a sentence to probation for the first time from January to June during 1996 and 1999, enabling a comparison of offenders before and after program implementation (Part 1, Juvenile Information System Data). Part 1 data include demographic data, prior charges, age at start of probation, detention use, reoffense, and commitment to Youth Corrections. Interviews with 168 court and corrections personnel were conducted in two interview rounds, from June to December 1999, and again from July to September 2000, soliciting their views of the sentencing guidelines, state supervision, and probation (Parts 2-3, Juvenile Justice System Personnel Interviews, Rounds 1 and 2). Interviews with 229 youth offenders obtained information on their involvement with and views of the sentencing guidelines, state supervision, and probation during a single interview in either the first or second round (Parts 4-5, Youth Offender Interviews, Rounds 1 and 2). A random sample of paper case files for pre- and post-guideline offenders was selected to analyze changes in contact and interventions provided (Part 6, Youth Offender Case File Analysis). These files were examined for documentation of contact frequency and type with offenders and their families and the number and types of programs used.